The Female Monster: The Pre-Catholic Manifestation as a Response to Modern Anxiety in Selected Stories by Nick Joaquin - Delos Reyes, Tyra (Archīum Ateneo, 2024)
Scholarship on the writings of Nick Joaquin have mostly concerned themselves with either their postcolonial resonances or the gender politics abound in the text. Tropical Gothic (1972) is widely read as an ambiguous approach toward feminism because of the depiction of the female as monstrous which has been argued to problematize its feminist possibilities, whether this depiction empowers or suppresses women in the texts. Examining the criticism of Marie Arong, Philip Holden, and Epifanio San Juan Jr., this paper asserts how existing notions of gender are able to produce a more nuanced reading of Nick Joaquin’s selected stories, specifically “Summer Solstice,” “Doña Jerónima,” and “The Order of Melkizedek.” This paper argues that while the attention to gender in the text is necessary, an exclusive treatment of the text with such a framework in mind is unfaithful to issues of the pre-Catholic and the modern that are equally resonant in the text. By using Jeffrey Cohen’s “Monster Culture (Seven Theses),” we demonstrate how the female and the feminine, by undergoing the female sacrifice and transforming into the monstrous, become a reaction to a modern anxiety toward the re-emergence of the pre- Catholic, and we reconcile the image of the female monster with her bond to nature through Sherry Ortner’s “Is Female to Nature as Male is to Culture?”. By firstly deconstructing notions of inherent female subversion in Joaquin’s selected texts, this paper is able to offer alternative ways of understanding the treatment of the female as the monster and, more importantly, see their transformation and self-sacrifice as a necessary element for the acceptance and understanding of the modern anxiety of the male characters around them, by becoming the monstrous hybrid of the pre-Catholic and the modern.